2016
DOI: 10.1063/1.4953147
|View full text |Cite
|
Sign up to set email alerts
|

Dark current analysis in high-speed germanium p-i-n waveguide photodetectors

Abstract: We present a dark current analysis in waveguide-coupled germanium vertical p-i-n photodetectors. In the analysis, surface leakage current and bulk leakage current were separated, and their activation energies were extracted. Surface leakage current originating from the minority carrier generation on the Ge layer sidewalls, governed by the Shockley-Read-Hall process and enhanced by the trap-assisted-tunneling process, was identified as the main contribution to the dark current of vertical p-i-n photodiodes at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…2019, 9,1901612 (hole) trap signal peaked at about 270 K. The trap energy, extracted via Arrhenius analysis of spectra from a range of different rate windows (as shown in the Figure 2a, inset), was found to be E T = E V + 0.56 eV, or lying within the bandgap and 0.56 eV above the valence band maximum. These data were collected at a 0.8 s −1 rate window across a 150-300 K temperature range and reveal a single majority carrier Adv.…”
Section: Figure 2amentioning
confidence: 99%
See 1 more Smart Citation
“…2019, 9,1901612 (hole) trap signal peaked at about 270 K. The trap energy, extracted via Arrhenius analysis of spectra from a range of different rate windows (as shown in the Figure 2a, inset), was found to be E T = E V + 0.56 eV, or lying within the bandgap and 0.56 eV above the valence band maximum. These data were collected at a 0.8 s −1 rate window across a 150-300 K temperature range and reveal a single majority carrier Adv.…”
Section: Figure 2amentioning
confidence: 99%
“…2019, 9,1901612 Table 1 presents average compositional fractions, along with associated standard deviations as conservative estimates of uncertainty, for each of the relevant elements (and combinations of elements) in both normal and defect regions. Energy Mater.…”
Section: Stem-based Chemical and Structural Defect Analysismentioning
confidence: 99%
“…Since the first successful implementation of this concept by Ahn, et al, a large number of architectures have been proposed and experimentally demonstrated. Ge homo-junction [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and Si-Ge-Si heterojunction [32,[35][36][37][38][39][40] photodetector arrangements have notably been evaluated. Both types of devices consist in pin junction arrangements, with a light absorption occurring in the intrinsic regions.…”
Section: Introductionmentioning
confidence: 99%
“…This results in slower responses, reduced photo-responsivities, and higher dark-currents in homo-junction structures [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In contrast, heterostructured Ge photodetectors with full Si via-contacts and doping scheme avoid Ge processing issues and might substantially simplify the process flow [32,[35][36][37][38][39][40]. For example, the same masking, ion implantation, and metal contacting steps can be used for the fabrication of active optical link components such as Si modulators and Si-Ge-Si photodetectors [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation